The Study of Indoor Lighting Quality in UTHM Kampus Bandar Building - Kimjus, Juventus Evan; Abd Wahab, Izudinshah (Recent Trends in Civil Engineering and Built Environment, 2021)
Lighting is an important element for us to see and carry out our daily routine. As for a building, it is important to have both natural lighting and artificial lighting. For a studio room, it requires a high amount of lighting so that visual task can be conduct effectively. The purpose of this research is to identify the level of natural and artificial light in Universiti Tun Hussein Onn Malaysia (UTHM) Kampus Bandar building. Based on preliminary observation, it is found that the natural lighting system in the Kampus Bandar are inadequate and has to rely on the artificial lighting. The expected result is to solve the lighting problem on the building and provide the best solution that helps to solve the problem. There are several factors that contribute to this problem such as inappropriate lighting levels, size and the location of the windows in buildings, and the location surrounding of the building. By using the Lux meter tools, the building was studied in accordance with MS1525:2014. The result shows that each studios has different illuminance level and the data are taken are divided into 22 points. Data taken starting from 9.00am, 12.30pm, and 4.30pm so that it can be analyze and compared to MS1515:2014. Studio room illumination level are lower than required illuminance level on MS1515:2014. However, the illumination level of each studio can increased with additional of artificial light.